Case Report: Durable complete response of advanced-stage hepatocellular carcinoma to DEB−TACE combined with lenvatinib and camrelizumab - Xu, Baiguo; Cui, Yufeng; Wang, Ning; Gao, Zhongsong; Ye, Qing; Xiang, Huiling (Frontiers in Immunology, 2025)
BackgroundHepatocellular carcinoma (HCC) with lung metastases is associated with a poor prognosis due to limited effective treatment options. Emerging evidence suggests that combining locoregional therapy, multi-kinase inhibitors (MKIs), and immune checkpoint inhibitors (ICIs) offers promising results for advanced HCC. However, the efficacy of innovative combinations of MKIs and ICIs remains inconclusive. Herein, we present a case of a patient with massive HCC and lung metastases, complicated with decompensated hepatitis B cirrhosis, who achieved complete remission (CR) lasting for 10 months following treatment with lenvatinib (an MKI), camrelizumab (a PD-1 inhibitor), and locoregional therapy.Case summaryA 58-year-old male patient with decompensated hepatitis B-induced liver cirrhosis and advanced HCC with lung metastases underwent drug-eluting bead transarterial chemoembolization (DEB-TACE) therapy. Initially, he received apatinib in combination with camrelizumab; however, due to intolerance to apatinib’s side effects, the regimen was adjusted to lenvatinib and camrelizumab. After three DEB-TACE sessions, 14 weeks of lenvatinib, and a 5-month course of camrelizumab, the patient achieved CR, with no tumor recurrence observed over 10 months of follow-up.ConclusionThe combination of DEB-TACE, lenvatinib, and camrelizumab demonstrated efficacy in a patient with advanced HCC and lung metastases. These findings suggest that integrating MKIs and ICIs may represent a potential treatment approach for select advanced HCC cases, warranting further validation in larger studies.